Assessment of fungicides for control of Fusarium head blight of winter barley in Georgetown, DE, 2025 - Shiv Singla; Alyssa K. Betts (Plant Health Progress, 2026)
Fusarium head blight (FHB), primarily caused by Fusarium graminearum, is a devastating disease of barley (Hordeum vulgare) worldwide. It results in bleached heads and shriveled, mycotoxin-contaminated grain, reducing both yield and grain quality. This report evaluates fungicide efficacy for FHB control in winter malting barley ‘Avalon’ in Georgetown, Delaware, in 2025. Disease incidence and severity, Fusarium-damaged kernels, yield, and deoxynivalenol levels were evaluated for all treatments. Results from these trials will help advise U.S. barley growers in developing management programs for this disease and should lead to a reduction of yield losses and mycotoxin levels in malting barley.